Mondor’s Disease - CM, Siti Kamariah; SC, Humairah (IIUM Medical Journal Malaysia, 2011)
A Mondor’s disease is a rare, benign and self-limiting condition. It is due to thrombophlebitis of the superficial veins of the breast and chest wall. It usually occurs in middle-aged women who present with a palpable cordlike structure, often painful in the acute phase. The aetiology is unknown, and may be related to trauma, surgery, infection or tight clothing. The finding of a superficial vessel seen as a linear opacity on mammography and a tubular structure on ultrasound is typical. An intra-luminal thrombus may be seen on ultrasound, and there may be absent flow on Doppler imaging. Conservative treatment is usually instituted, although surgery may be indicated in certain circumstances.